2018
DOI: 10.3389/fncel.2018.00440
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Effects of Metformin on an Inflammatory Model of Parkinson’s Disease

Abstract: The oral antidiabetic drug metformin is known to exhibit anti-inflammatory properties through activation of AMP kinase, thus protecting various brain tissues as cortical neurons, for example. However, the effect of metformin on the substantia nigra (SN), the main structure affected in Parkinson’s disease (PD), has not yet been studied in depth. Inflammation is a key feature of PD and it may play a central role in the neurodegeneration that takes place in this disorder. The aim of this work was to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 92 publications
0
30
0
Order By: Relevance
“…In their studies, de Pablos and colleagues have used a week therapy with MTF (150 mg/kg, p.o., twice daily dosage) in an MPTP-induced PD model and a model of dementia and showed a neuronal harming action of MTF. Hence, a warning conclusion was released for the possibility of the pathogenic role of MTF in neurodegenerative conditions (Ismaiel et al, 2016;Tayara et al, 2018). Based on the data reported by Patil et al (2014), the neuroprotective role of MTF (500 mg/kg, p.o.)…”
Section: Discussionmentioning
confidence: 99%
“…In their studies, de Pablos and colleagues have used a week therapy with MTF (150 mg/kg, p.o., twice daily dosage) in an MPTP-induced PD model and a model of dementia and showed a neuronal harming action of MTF. Hence, a warning conclusion was released for the possibility of the pathogenic role of MTF in neurodegenerative conditions (Ismaiel et al, 2016;Tayara et al, 2018). Based on the data reported by Patil et al (2014), the neuroprotective role of MTF (500 mg/kg, p.o.)…”
Section: Discussionmentioning
confidence: 99%
“…Hence, AMPK activators, shifting the energy balance toward reduction of ATP consumption, along with the enhanced mitophagy and prevention of α-synuclein aggregation, can act as possible PD-modifying drugs. Although no results from clinical trials with metformin in PD patients have so far been reported, there is preclinical evidence that AMPK activation in neurons is protective, and the treatment with metformin can ameliorate symptoms and pathology in animal models of toxin-induced PD [ 182 , 183 ]. In 2017, a pilot study on patients diagnosed with mild cognitive impairment or early AD showed that treatment with metformin improved executive function, learning and memory [ 184 ].…”
Section: Pharmacological Control Of Autophagymentioning
confidence: 99%
“…Metformin supplementation ameliorates the signs of stroke, cytokine levels, and neutrophil infiltration in the brains of mice subjected to medial cerebral artery occlusion by activating the AMPK pathway and inhibiting NF-κB signaling [146,147]. In contrast, in an inflammatory model of PD consisting of intranigral injection of LPS, metformin ameliorates microglial activation and cytokine secretion, but exacerbates the death of dopaminergic neurons [148]. These detrimental effects may arise from the fact that metformin is a weak inhibitor of the mitochondrial complex I [149], whose deficiency has been clearly linked to PD development [150].…”
Section: Metforminmentioning
confidence: 99%